Surgical technique and functional results of irreparable cuff tears reconstructed with the long head of the biceps tendon - (:unkn) unknown (My University, 2001)
The purpose of the study was to evaluate the results obtained from patients who were treated with open surgical technique using the long head of the biceps tendon for irreparable tears of the rotator cuff tendons. Between May 1992 and January 1997, 14 patients underwent rotator cuff reconstruction of irreparable tears at our clinic. These patients were evaluated before and after a minimum follow-up of 26 months (mean: 40.2 months) following surgery with the Constant's functional score. The long heads of the biceps tendons were found to be hypertrophied in all 14 shoulders and in 10 of them they were also subluxated. After re-seating the surgically enlarged biceps tendon onto the center of the uncovered head region, the biceps tendon to cuff tendon repair and the biceps tenodesis were done in all shoulders. The mean functional Constant's score before surgery was 46.7 points (poor) and the mean postoperative score at the final follow-up was 75.35 points (good). Satisfactory results were achieved in 85.7% of the patients. These results suggest that this surgical technique can be used to attain a painless and functional shoulder after irreparable cuff tear reconstruction.
Keywords: Female; Humans; Middle Aged; Treatment Outcome; Aged; Male; Follow-Up Studies; Range of Motion, Articular; Tendons; Rotator Cuff; Rotator Cuff Injuries; Splints